Spinal anaesthesia for laparoscopic cholecystectomy: A feasibility and safety study - Gautam, B (Kathmandu University Medical Journal, 2010)
Background: Regional anaesthetic techniques have benefited those patients undergoing laparoscopic surgeries that are deemed high risk to receive general anaesthesia (GA). But spinal anaesthesia (SA) has not been routinely employed as the sole technique for laparoscopic cholecystectomy (LC). Objective: This study was conducted to uncover feasibility and safety of SA for conducting LC. Materials and methods: Twelve American Society of Anaesthesiologists' physical status I or II patients undergoing elective LC received SA using 4 ml of 0.5% hyperbaric Bupivacaine mixed with 0.15 mg Morphine. Peri-operative preparations and management were all standardised, with other drugs being only administered to manage anxiety, pain, nausea/vomiting, hypotension, and any adverse event. LC was performed with CO2 pneumoperitoneum maintained at an intra-abdominal pressure of less than 10 mm Hg and with minimal operating table tilt. Peri-operative events, operative difficulty, hospital stay and patient satisfaction were studied. Results: Spinal anaesthesia was adequate for surgery in all but one patient. Intraoperatively, two out of four patients who experienced right shoulder pain received Fentanyl. Two patients were given Midazolam for anxiety and one was given Ephedrine for hypotension. Operative difficulty scores were minimal and surgery in one patient was converted to open cholecystectomy. Postoperatively, pain scores were minimal and no patient demanded opioid. One patient required antiemetic for vomiting and one patient each suffered headache and urinary retention. 11 patients were discharged within 48 hours of surgery and patient satisfaction scores were very good. Conclusion: Spinal anaesthesia with Morphine-mixed hyperbaric Bupivacaine is adequate and safe for elective LC in otherwise healthy patients and minimises postoperative pain and opioid use. Success and safety of this technique, however, necessitates knowledgeable patient, gentle surgical procedure, and co-operation among patient and members of the perioperative care team. Key words: Hyperbaric Bupivacaine; intrathecal Morphine; laparoscopic cholecystectomy; spinal anaesthesia. DOI: 10.3126/kumj.v7i4.2755 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 360-368